William Montgomery Watt as an Interpreter of the Holy Qur’an - Dr. Tariq Aziz; Dr. Hafiz Muhammad Abrar Awan; Dr. Muhammad Shahbaz Manj; Dr. Ahmad Hassan Khattak; Dr. Saima Munir (Al-Qanṭara, 2022)
Abstract Majority of the Orientalists consider the Holy Qur’an as the primary source of Islamic faith, worship and teachings, so most of them have tried their best to make Qur’an unauthentic and contradictory. For that purpose, they have directed to devote all their efforts to prove it an unauthentic book. Quranic commentaries (tafāsīr) have always been at the center of Islamic intellectual history, the prism through which the Quran has been mediated to believers. In this regard, Montgomery Watt is a Scottish Orientalist who has published his commentary of the Holy Qur’an. In this paper, efforts are made to present an evaluation of his Qur’an interpretation. The present assessment aims at bringing out strengths and weaknesses of his Qur’an Commentary. It is perceived that the Holy Qur’an is free from any human error and textual amendment but at that point, Montgomery Watt tries to get benefit from diverse and somehow weak Tafsīr literature. Therefore, this study recommends that Muslim scholars must respond to the objections and reservations of the western scholars such as W. Montgomery Watt in their research work. In this study, analytical research methodology has been adopted with a qualitative approach.